The Oxford Handbook of Governance - Edited by Levi-Faur, David (Oxford Oxford University Press, 2014)
This Oxford Handbook will be the definitive study of governance for years to come. 'Governance' has become one of the most popular terms in contemporary political science; this Handbook explores the full range of meaning and application of the concept and its use in a number of research fields.
Include References and Index
Keywords: Political science -- Policy sciences